Optimal institutions for monetary policy: Contracts, shocks and signaling - Hans Peter Grüner (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
The effects of different institutional arrangements for the central bank are examined in the presence of economic shocks and uncertainty about the central banker's and the medianvoter's inflation target. A contract which is based on self-imposed monetary target announcements proves to be superior to the best monetary rule if conflicts about the inflation target within society are relatively small compared to the initial uncertainty about the medianvoter's objective. It is superior to the laissez faire solution if unemployment exceeds a certain threshold level. The optimal choice of costs of deviations from auto-imposed targets depends on the type of conflict within society, whether the individuals disagree on the weight of the inflation versus the employment target or on the value of the inflation target itself.
Keywords: E50; E52; E58; 330; signaling; monetary target announcements; monetary rules; Geldpolitik; Ankündigungseffekt; Schock; Regelbindung; Ökonomische Theorie der Demokratie; Theorie